EXECUTIVE APOLOGIES FOR PRICE FIXING: ROLE BIASED PERCEPTIONS OF CAUSALITY - Sonnenfeld, Jeffrey (Academy of Management Journal, 1981)
The article discusses the results of a research which demonstrated how discrepant but systematic executive perceptions blur the clarity of organizational learning. In the study, executives in several companies were asked to explain the involvement of their companies in a price fixing conspiracy. The author notes that the role bias examined was the difference in perceptions between senior level executives and divisional executives formed six months after conspiracy convictions had been made and court sentencing had been handed down. The results showed that the corporate executives believed the blame was because of dispositional factors, while divisional executives believed it was attributable to situational factors.